Living in fear: How experience shapes caribou responses to predation risk - Laurie Derguy; Mathieu Leblond; Martin‐Hugues St‐Laurent (Ecosphere)
Abstract Wild prey can reduce predation risk by avoiding areas used by their predators. As they get older, individuals should be able to fine‐tune this avoidance based on their increased experience with predation risk. Such learning mechanisms are expected to play a key role in how individuals cope with risk during their life, particularly in altered landscapes where human disturbances have created habitat conditions distinct from those of the past. We studied the role of experience on the avoidance of risky areas by boreal caribou (Rangifer tarandus caribou) in a system where they are under high predation pressure from gray wolves (Canis lupus) and black bears (Ursus americanus). Using telemetry data collected on 28 caribou, 31 wolves, and 12 bears, we investigated whether caribou adjusted their level of predator avoidance with passing monitoring years, a proxy of increasing experience. We observed an increase in the avoidance of areas suitable to wolves (during two study periods) and bears (during all study periods) with passing years. Periods during which caribou did not adjust their behavior toward wolves (winter and calving) were characterized by persistent—potentially innate—avoidance. Our results suggest that, in most circumstances, caribou became more efficient at avoiding areas selected by their predators as they gained experience. Future work should attempt to demonstrate whether such tactics are heritable; if so, our results would suggest that, given time, caribou living in disturbed environments would have the potential to adapt to changing levels of risk. This would give hope for the conservation of caribou, a species at risk in Canada, provided levels of risk do not surpass the limits of their behavioral plasticity.